STRATEGIES FOR FORMING MEDIA COMPETENCE BASED ON BLENDED LEARNING - Tog’ayeva Muattar Bahodir qizi (TADQIQOTLAR, 2026)
Annotation: The rapid digitalization of education has significantly increased the importance of media competence as a key component of students’ professional and personal  development.  This  article  explores  effective  strategies  for  forming  media competence  through  blended  learning,  which  integrates  traditional  face-to-face instruction  with  digital  and  online  learning  environments.  The  study  analyzes theoretical foundations, pedagogical approaches, and practical methods for developing media  literacy,  critical  thinking,  and  digital  communication  skills.  The  research employs  qualitative  and  mixed-method  approaches,  including  observation,  surveys, and  experimental  teaching.  Results  indicate  that  blended  learning  environments enhance students’ ability to critically evaluate media content, produce digital materials, and  engage  in  interactive  learning  processes.  The  article  concludes  with recommendations  for  educators  and  institutions  to  optimize  media  competence development through blended learning models.